Pengaruh Penerapan Problem Based Learning Berbantuan Google Classroom terhadap Hasil Belajar pada Mata Pelajaran Informatika Materi Teknik Komputer di SMA Negeri 2 Kuningan - Annisa Nurul Fitri (Journal of Informatics and Vocational Education, 2020)
This research aims to improve learning outcomes in the Informatika subject on Teknik Komputer through the application of Problem Based Learning assisted by online discussions through google classrooms during the Covid 19 pandemic with doing learning as synchronously and asynchronously. These research subjects are students of class X MIPA 1 at SMA Negeri 2 Kuningan. The method used in this research is classroom action research with the stages of planning, implementation, observation and reflection. Data collection techniques using tests and observations. From the research results, learning outcomes have increased each cycle, in the pre-cycle students only achieved learning completeness by 25%, cycle I increased to 58%, cycle II was 61% and in cycle III completeness increased to 86%. From this research, it can be concluded that the application of Problem Based Learning assisted by online discussions through google classroom can improve student learning outcomes in Teknik Komputer material in Informatika subjects in class X MIPA 1 at SMA Negeri 2 Kuningan.